2008
DOI: 10.1007/s00213-008-1439-6
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing and subjective effects of methylphenidate in adults with and without attention deficit hyperactivity disorder (ADHD)

Abstract: Rationale There has been controversy over the abuse potential of methylphenidate (MPH) in the context of treatment for attention deficit hyperactivity disorder (ADHD). Objective The objective of this study was to compare the reinforcing and subjective effects of oral MPH in adults with and without ADHD. Materials and methods Following screening, 33 adults (n= 16 with ADHD; n=17 free from psychiatric diagnoses) completed four pairs of experimental sessions, each of which included a sampling session and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…The function of the dopamine transporter and consequently the effects of methylphenidate appear to be altered in individuals with ADHD compared with those in individuals without the disorder (Mazei-Robison et al, 2008). Consistent with that finding, self-administration of methylphenidate in humans produced reinforcing effects in normal adults but not in adult subjects with ADHD (Kollins et al, 2009). Further studies must be conducted to determine whether the observed effects of the drug in this study also reflect the drug's effects in ADHD or are limited to the normal brain.…”
Section: Downloaded Fromsupporting
confidence: 58%
“…The function of the dopamine transporter and consequently the effects of methylphenidate appear to be altered in individuals with ADHD compared with those in individuals without the disorder (Mazei-Robison et al, 2008). Consistent with that finding, self-administration of methylphenidate in humans produced reinforcing effects in normal adults but not in adult subjects with ADHD (Kollins et al, 2009). Further studies must be conducted to determine whether the observed effects of the drug in this study also reflect the drug's effects in ADHD or are limited to the normal brain.…”
Section: Downloaded Fromsupporting
confidence: 58%
“…Alternatively, healthy individuals may choose to use this drug because of its subjective effect on perception of self confidence, [11] sense of concentration, [15] alertness and vigor, fatigue [6,8], mood [6] and well being [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies completed with normal adults ) and adults with a history of recreational stimulant use (Parasrampuria et al 2007) suggest that positive subjective effects, which are considered indicators of abuse liability, are significantly lower for OROS-MPH compared with immediate release (IR)-MPH. Laboratory doubleblind choice procedure and self-administration studies of IR-MPH in children and adults with ADHD suggest that although individuals with ADHD choose IR-MPH more than placebo, this selection is related to the therapeutic, rather than the euphoric, effects of the medication Kollins 2004, 2005;Kollins et al 2009). Given the generally low abuse liability of OROS-MPH, it was predicted that the euphoric subjective effects of OROS-MPH would not differ significantly from those of placebo and would not differ as a function of baseline substance use severity and that adolescent ratings would not significantly differ from adult ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that the likeability of psychostimulants in individuals with ADHD is associated more with therapeutic effect than with euphoric effects Kollins 2004 2005;Kollins et al 2009). Results from the present analyses are consistent with this research in that the correlation between medication liking and treatment effectiveness was stronger than the correlation between liking and high for both the adolescent and adult samples.…”
mentioning
confidence: 99%